Isolation of a novel simian T-cell lymphotropic virus from Pan paniscus that is distantly related to the human T-cell leukemia/lymphotropic virus types I and II. - Giri, A (1994)
An unusual serological profile against human T-cell leukemia/lymphotropic virus type I and II (HTLV-I and -II) proteins was reported in several human Pygmy tribes in Zaire and Cameroon with serum antibodies reactive with gp21 and p24. Here we describe a similar pattern of serum antibodies in a colony of captive pygmy chimpanzees and the isolation of a novel retrovirus, simian T-cell lymphotropic virus from Pan paniscus (STLVpan-p), from the peripheral blood mononuclear cells of several seropositive animals. Cocultures of peripheral blood mononuclear cells from three seropositive pygmy chimpanzees with human cord blood mononuclear cells led to the expression of an HTLV-I- and HTLV-II-related virus initially demonstrated by electron microscopy. Furthermore, several of these cocultures became immortalized T-cell lines expressing the CD4+ CD8+ DR+ phenotype of mature activated T cells. Southern blotting and DNA sequencing of a PCR fragment of viral DNA from these cell cultures demonstrated a distant evolutionary relationship of these viruses to HTLV-I and -II and distinct from the known STLV isolates. We designated this virus STLVpan-p. A genealogical analysis of the captive pygmy chimpanzees colony, originated from wild-caught animals, revealed a prevalence of seropositive offspring from infected mothers, as also observed with HTLVs. The presence in this old African Great Ape species of a virus which is genetically quite distinct from HTLV-I and -II could provide new insights in the phylogenesis of STLVs and HTLVs and be instrumental in the discovery of related human viruses.